An attempt to evaluate the criteria for diagnosing nonspecific inflammatory diseases observed on ancient skeletons - Prejzner, Witold; Gładykowska-Rzeczycka, Judyta J. (Anthropological Review, 1997)
The study presents the criteria for diagnosing nonspecific inflammatory diseases observed on ancient bones. It is very important to remember about two forms of ostitis - acute and chronic, and about diseases causing similar changes, e.g. tuberculosis, lues, brucelosis, cysts, osteoid-osteoma.